2019
DOI: 10.1177/1758835919859990
|View full text |Cite
|
Sign up to set email alerts
|

Third-line systemic treatment in advanced/metastatic gastric cancer: a comprehensive review

Abstract: The management of advanced gastric cancer has improved over the past decade. There is more evidence to support the efficacy of systemic treatment in refractory gastric cancer beyond second-line treatment. Important randomized controlled trials of chemotherapies, targeted agents and immunotherapies have been reported. With the development of these novel therapies, clinicians can better individualize treatment for patients beyond progression on second-line therapy. However, there is no guideline on third-line th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…5), which is typical of the AEs often associated with third-line chemotherapy options used worldwide in advanced gastric cancer (i.e. neutropenia, anaemia, thrombocytopenia, fatigue and anorexia) [3, 27]. Treatment-related grade ≥ 3 AEs were reported in approximately half of the trifluridine/tipiracil recipients and more than four times more frequently than in the placebo group (Sect.…”
Section: Current Status Of Trifluridine/tipiracil In Metastatic Gastrmentioning
confidence: 99%
See 1 more Smart Citation
“…5), which is typical of the AEs often associated with third-line chemotherapy options used worldwide in advanced gastric cancer (i.e. neutropenia, anaemia, thrombocytopenia, fatigue and anorexia) [3, 27]. Treatment-related grade ≥ 3 AEs were reported in approximately half of the trifluridine/tipiracil recipients and more than four times more frequently than in the placebo group (Sect.…”
Section: Current Status Of Trifluridine/tipiracil In Metastatic Gastrmentioning
confidence: 99%
“…The aim of treating metastatic gastric cancer is to prolong survival and maximize health-related quality of life (HR-QOL). Unresectable metastatic gastric cancer has traditionally been treated with palliative therapies in combination with best supportive care (BSC) [2, 3]. These regimens can include fluoropyrimidine- [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…GC is a gastrointestinal malignant tumor and a main cause of cancer-associated death worldwide. Although GC can be cured by surgery in the early stages, many patients lose the opportunity for surgery at the time of the diagnosis 74 . Therefore, the exploration of novel diagnostic biomarkers and treatment strategies will be of great help to us.…”
Section: Cirs-7 In Various Human Cancersmentioning
confidence: 99%
“…Gastric cancer (GC) is the fifth most common cancer with over 1,000,000 new cases annually, and also the third leading cause of cancer mortality worldwide (1). Despite that interventional endoscopic therapy or surgeries make early-stage GC curable, many late-stage patients have already been subject to local advancement and/or metastasis (stage IV) at diagnosis, losing chances of radical therapy (2,3). Traditionally, multiline sequential chemotherapy is the standard treatment principle for unresectable late-stage GC patients (4).…”
Section: Introductionmentioning
confidence: 99%
“…ICI treatment could efficaciously rescue anergic immune cells and restart the host anti-tumor immune response. Pembrolizumab (Keytruda) and nivolumab (Opdivo) are two anti-PD-1 monoclonal antibodies which have gained approval for the third-line treatment of locally advanced and/or metastatic GC patients due to the encouraging results of Keynote-059 and Attraction-2 (2,3). Current evidence indicated that Epstein-Barr virus (EBV)-related, mismatch repair (MMR) deficient or PD-L1 highly expressed GC have better response to immunotherapy in contrast to other subtypes in terms of overall response rate (ORR), progression-free survival (PFS) and overall survival (OS) (6,7).…”
Section: Introductionmentioning
confidence: 99%